1998
DOI: 10.1159/000017970
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Glycerol on the Protective Function of the Horny Layer against Irritants and on the Penetration of Hexyl Nicotinate

Abstract: Background: It is known that glycerol in an oil-in-water emulsion has a protective effect against irritating substances. Objective: To answer the question: is the protection effect of glycerol based on a regenerative process? Methods: Upon irritation by either tape stripping or acetone treatment, we applied glycerol to the skin surface under an occlusive dressing to create transepidermal water movement. As a control we used water under the occlusive dressing on the contralateral forearm. After 5 h we compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 20 publications
(15 reference statements)
2
28
1
2
Order By: Relevance
“…Investigations have also been made concerning the mechanism of barrier improvement after glycerol [38]: irritation of the skin was first provoked by tape stripping or by acetone treatment. Then 85% glycerol or water was Gloor applied, followed by occlusive treatment for 5 h. Using various methods (dimethyl sulfoxide test, alkali resistance, SLS test), it could be shown that the barrier regenerated faster under the influence of glycerol.…”
Section: Effect Of Glycerolmentioning
confidence: 99%
“…Investigations have also been made concerning the mechanism of barrier improvement after glycerol [38]: irritation of the skin was first provoked by tape stripping or by acetone treatment. Then 85% glycerol or water was Gloor applied, followed by occlusive treatment for 5 h. Using various methods (dimethyl sulfoxide test, alkali resistance, SLS test), it could be shown that the barrier regenerated faster under the influence of glycerol.…”
Section: Effect Of Glycerolmentioning
confidence: 99%
“…Thus, the selection of galenic preparation is essential for optimal therapeutic results of topically applied substances [12][13][14]22] .…”
Section: Discussionmentioning
confidence: 99%
“…Also the hygroscopic alcohol glycerin, not a physiological component of the skin, is useful in bringing moisture back into dry skin. 56 The replaced moisturizers, however, with only last till the next wash or the next overhydrating glove work, if they are not protected by an adequate lipid layer.…”
Section: Moisturizer Replacementmentioning
confidence: 99%